2020
DOI: 10.1111/pcn.12972
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness practice alters brain connectivity in community‐living elders with mild cognitive impairment

Abstract: Aim There is increasing evidence that mild cognitive impairment (MCI) is associated with widespread brain dysconnectivity. Mindfulness practice, which involves focused attention to experience the present moment in a purposeful way, has been shown to confer positive psychological and functional brain changes in healthy practitioners. It is unclear whether mindfulness practice could improve functional brain connectivity in older adults with cognitive impairment. Methods Forty‐seven participants with MCI were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…Dysfunction of the STG may result in the impairment of language and social skills in MCI. Localized changes of the STG were present after mindfulness practice for three months in subjects with MCI (Fam et al, 2020 ). The insula, especially the anterior insula, is a critical node of the SN which connects many areas including the prefrontal cortex and the parietal lobe and engages in the transformation between cognitive domains (Cerliani et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the STG may result in the impairment of language and social skills in MCI. Localized changes of the STG were present after mindfulness practice for three months in subjects with MCI (Fam et al, 2020 ). The insula, especially the anterior insula, is a critical node of the SN which connects many areas including the prefrontal cortex and the parietal lobe and engages in the transformation between cognitive domains (Cerliani et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…50 However, in a more recent study, adults with mild cognitive impairment showed improvements in verbal memory following a 3-month mindfulness intervention, compared with a control group. 51…”
Section: Effects Of Mindfulness On Cognition In Mild Cognitive Impairmentmentioning
confidence: 99%
“…In one, participants with amnestic mild cognitive impairment in both a mindfulness intervention and a psychoeducational control group improved on measures of anxiety, depression, and aging-related quality of life over 8 weeks at posttreatment and at a 3-month follow-up. 50 In the second study, both a mindfulness awareness and a health education intervention reduced depression and anxiety at trend levels among older adults with mild cognitive impairment, although greater benefits were observed for the health education group 47 (Table 1 [45][46][47][48][49][50][51][52] ).…”
Section: Effects Of Mindfulness On Mood In Mild Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other controlled trials of mindfulness meditation in generally healthy elders [86][87][88], stressed older adults [89], elders with MCI [90][91][92], dementia caregivers [93] and nursing home residents [94], showed little or no improvement in cognitive measures, nor did trials of therapist-delivered music programs in Italian elders with memory loss [95] and psychiatric in-patients with cognitive impairment [96] or of passive music listening in Taiwanese AD patients [97]. Cognitive gains observed with simple KK and ML in this study are comparable to those reported with tai chi [98][99][100], conventional exercise [99,101], cognitive training [102,103], and multicomponent interventions [104][105][106] in older adults with and without cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%